Clinical, molecular, and radiomic profile of gliomas with FGFR3-TACC3 fusions. Issue 11 (15th May 2020) - Di Stefano, Anna Luisa; Picca, Alberto; Saragoussi, Edouard; Bielle, Franck; Ducray, Francois; Villa, Chiara; Eoli, Marica; Paterra, Rosina; Bellu, Luisa; Mathon, Bertrand; Capelle, Laurent; Bourg, Véronique; et al.
Abstract: Background: Actionable fibroblast growth factor receptor 3 ( FGFR3 )–t ransforming acidic coiled-coil protein 3 fusions ( F3T3 ) are found in approximately 3% of gliomas, but their characteristics and prognostic significance are still poorly defined. Our goal was to characterize the clinical, radiological, and molecular profile of F3T3 positive diffuse gliomas. Methods: We screened F3T3 fusion by real-time (RT)-PCR and FGFR3 immunohistochemistry in a large series of gliomas, characterized for main genetic alterations, histology, and clinical evolution. We performed a radiological and radiomic case control study, using an exploratory and a validation cohort. Results: We screened 1162 diffuse gliomas (951 unselected cases and 211 preselected for FGFR3 protein immunopositivity), identifying 80 F3T3 positive gliomas. F3T3 was mutually exclusive with IDH mutation ( P < 0.001) and EGFR amplification ( P = 0.01), defining a distinct molecular cluster associated with CDK4 ( P = 0.04) and MDM2 amplification ( P = 0.03). F3T3 fusion was associated with longer survival for the whole series and for glioblastomas (median overall survival was 31.1 vs 19.9 mo, P = 0.02) and was an independent predictor of better outcome on multivariate analysis. F3T3 positive gliomas had specific MRI features, affecting preferentially insula and temporal lobe, and with poorly defined tumor margins. F3T3 fusion was correctly predicted by radiomics analysis on both the exploratory (area under the curve [AUC] = 0.87) and the validation MRI (AUC = 0.75) cohort. Using Cox proportional hazards models, radiomics predicted survival with a high C-index (0.75, SD 0.04), while the model combining clinical, genetic, and radiomic data showed the highest C-index (0.81, SD 0.04). Conclusion: F3T3 positive gliomas have distinct molecular and radiological features, and better outcome.